2023
DOI: 10.1002/pc.27248
|View full text |Cite
|
Sign up to set email alerts
|

Response of extreme environmental aging on the novel Moringa stenopetala husk fiber/epoxy composites: Understanding the characteristics and thermokinetic behavior

Abstract: The increasing use of composite components in various engineering disciplines necessitates detailed comprehension of their operation. When subjected to adverse environmental circumstances, such as variable humid surroundings and UV radiations, the structural and mechanical characteristics of the composites can deteriorate. Additionally, using these composite materials for structural applications such as rooftop buildings or household properties may reduce lifespan. In this study, the static and dynamic mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 139 publications
0
1
0
Order By: Relevance
“…14 Their investigations concluded that 15 wt.% of cellulose particulates from pod waste of Moringa oleifera fruit reinforcement in epoxy bio-composite maximizes its mechanical properties. The ground dried leaves of Moringa oleifera were used as reinforcement filler in epoxy composite by Kajal et al 15 They adopted the hand layup technique to fabricate the composites and their findings conclude the optimum wt.% of ground dried leaves of Moringa oleifera in the polymer composite as 20 wt.%. The optimum loading of ground dried leaves of Moringa oleifera in the polymer composite maximized its water absorption and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…14 Their investigations concluded that 15 wt.% of cellulose particulates from pod waste of Moringa oleifera fruit reinforcement in epoxy bio-composite maximizes its mechanical properties. The ground dried leaves of Moringa oleifera were used as reinforcement filler in epoxy composite by Kajal et al 15 They adopted the hand layup technique to fabricate the composites and their findings conclude the optimum wt.% of ground dried leaves of Moringa oleifera in the polymer composite as 20 wt.%. The optimum loading of ground dried leaves of Moringa oleifera in the polymer composite maximized its water absorption and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%